Pembangunan Aplikasi Iqro' Berbasis Android Menggunakan Google Speech - Ach Fauzan; Issa Arwani; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Learn the Al-Quran (reciting Al-Quran) is the obligation of every Moslem. To be able to reciting Al-Quran properly begins with getting to know about hijaiyah letters (the arabic letters) using Iqro' methods. Iqro is a method of learning to know about hijaiyah letter developed by H. As'ad. This method is very popular among Indonesian community. In order to make the learning process isn't boring is required a learning media that can be used anytime, one of them are using a mobile device application that can be used via smartphone. This research describes how to build a media applications to learning Iqro' based on android and integrate it with google speech so that applications built more interesting and interactive with users. Google speech be integrated on a test feature, users are asked to answer each question using their speech then google speech function to convert their voice to text. Text results obtained then matched with answer keys, by involving the user in question features, make this applications more interactive. Results of testing the accuracy of google speech's implementation of the question features stated that on the final test showed 100%, that means it's been as expected.